2015
DOI: 10.1089/bari.2015.0004
|View full text |Cite
|
Sign up to set email alerts
|

Does Age Influence Bariatric Surgery Outcomes?

Abstract: Aim: The purpose of this study was to evaluate presurgical comorbidities, perioperative and postoperative complications, and postsurgical outcomes of minimally invasive bariatric surgery in patients aged 55 years and older to determine if age should be used as a selection criteria for bariatric surgery. Methods: A total of 750 patients underwent sleeve gastrectomy or robotic-assisted Roux-en-Y gastric bypass from January 2008 to June 2014. Patients were divided into three groups according to age: <55 years old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…Nonetheless, as the amount of clinical evidence enlarged, it became recognizable that the surgical outcomes of bariatric surgery, including morbidity and mortality rates, in older patients were not significantly different than those observed in younger ones ( 28 31 ). Thus, the number of bariatric procedures performed in older patients has increased over the past decades ( 32 , 33 ). Our data not only reinforces that weight loss achieved after RYGB in patients over 50 years old are not inferior to the observed in younger patients, but also suggests that the CV benefits in this patient group as compared to the younger ones are also more likely to be superior.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, as the amount of clinical evidence enlarged, it became recognizable that the surgical outcomes of bariatric surgery, including morbidity and mortality rates, in older patients were not significantly different than those observed in younger ones ( 28 31 ). Thus, the number of bariatric procedures performed in older patients has increased over the past decades ( 32 , 33 ). Our data not only reinforces that weight loss achieved after RYGB in patients over 50 years old are not inferior to the observed in younger patients, but also suggests that the CV benefits in this patient group as compared to the younger ones are also more likely to be superior.…”
Section: Discussionmentioning
confidence: 99%
“…Of 38 studies comparing the safety of bariatric procedures in older vs younger groups, 16 found no difference in early mortality or complication rates between groups . A further four studies found no difference between groups in overall complications, but higher rates of certain events in older participants, such as cardiac complications, intubation for longer than 48 hours, acute kidney injury, sepsis and pulmonary embolus, and bleeding .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 28 studies in which weight outcomes for older and younger persons were compared, 16 found no significant difference in weight loss between groups, and seven studies reported less weight loss in older than younger participants . Greater total weight loss in younger participants but no difference in percent excess weight loss (%EWL) between groups was reported in two studies .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations